Ordered platinum alloy catalyst, preparation method and fuel cell
By introducing low-melting point metals and polymer additives into the Pt alloy catalyst to form a carbon-covered structure, the problem of agglomeration and growth of Pt alloys during the formation of an orderly structure is solved, and an orderly platinum alloy catalyst is achieved at low temperatures The preparation of the catalyst improves the stability and performance.
Patent Information
- Application Number
- CN202411157164.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2024-12-13
AI Technical Summary
The existing Pt alloy catalysts are prone to agglomeration and growth during the formation of an ordered structure, resulting in a decrease in electrochemical activity and a decrease in batch consistency, making it difficult to prepare an ordered structure at low temperatures.
The ordered platinum alloy catalyst with the core PtMM* alloy and C and the outer shell is a carbon layer. The preparation is reduced by the coordinated auxiliary preparation of polymer additives and low-melting metal elements to reduce the bonding strength between platinum and alloy components. , avoid agglomeration and growth caused by high-temperature heat treatment, and realize the preparation of ordered alloys at low temperatures.
Prepare an ordered platinum alloy catalyst with small particle size and uniform particle size at low temperature, which improves the durability and stability of the catalyst, enhances catalytic activity and selectivity, reduces the consumption of precious metal platinum, and improves the performance of fuel cells .
Smart Images

Figure CN119133489A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fuel cell technology, and in particular to an ordered platinum alloy catalyst, a preparation method and a fuel cell. Background Art
[0002] Fuel cells have become the optimal solution for electrification in the heavy-duty field due to their high energy density, long driving range, and zero emissions during the operation phase. A typical representative of hydrogen fuel cells is the proton exchange membrane fuel cell (PEMFC), whose core component is the membrane electrode (MEA), which consists of a proton exchange membrane (PEM) located in the center, a catalyst layer (CL) coated thereon, and a gas diffusion layer (GDL) on the outside. Among them, the main components of the catalytic layer are Pt / C catalyst and perfluorosulfonic acid ion polymer (ionomer), and are divided into positive and negative poles, where the cathode is used to catalyze the oxygen reduction reaction (ORR) and the anode is used to catalyze the hydrogen oxidation reaction (HOR). Since the ORR process is a four-electron process, the kinetics are slow compared to the HOR, which becomes a bottleneck restricting the power generation performance of MEA.
[0003] As a widely used ORR catalyst, Pt / C catalyst has the problem of high cost. It is necessary to reduce the amount of Pt by alloying with non-precious metals. In addition, by forming a Pt alloy catalyst through non-precious metal doping, the d electron band center of Pt can be regulated, the adsorption energy for oxygen reduction intermediates can be improved, the reaction energy barrier can be reduced, and the ORR catalytic activity can be jointly improved through surface strain regulation. At the same time, in order to improve the durability and stability of Pt alloy catalysts, it is necessary to construct an ordered structure of intermetallic compounds, which are characterized by low formation energy and high cohesive energy, and can be more suitable under the fuel cell membrane electrode working conditions. However, in the process of forming an ordered structure, it is necessary to overcome extremely high diffusion energy barriers, so it depends on high-temperature heat treatment to achieve it. High-temperature heat treatment can easily cause the agglomeration and growth of Pt alloys, thereby reducing the electrochemical active area and mass activity of the catalyst, and causing the batch consistency of the catalyst to decrease. Therefore, how to avoid the agglomeration and growth of Pt alloys in the process of forming an ordered structure of Pt alloy catalysts is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The present application provides an ordered platinum alloy catalyst, a preparation method and a fuel cell to solve the following technical problem: how to avoid agglomeration and growth of Pt alloy in the process of forming an ordered structure of the Pt alloy catalyst.
[0005] In a first aspect, the present application provides an ordered platinum alloy catalyst, the catalyst comprising:
[0006] A core, wherein the core is a composite of a PtMM* alloy and C, wherein M is a non-precious metal and M* is a low melting point metal; and
[0007] The outer shell is coated on at least a portion of the surface of the inner core, and the outer shell is a carbon layer.
[0008] Optionally, the non-precious metal includes one or more of aluminum, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc and germanium.
[0009] Optionally, the low melting point metal includes one or more of gallium, indium, tin and bismuth.
[0010] Optionally, the molar ratio of Pt, M and M* is (3-13):(0.5-1.5):(0.5-1.5).
[0011] Optionally, the catalyst meets at least one of the following properties: particle size <5 nm, mass activity ≥400 mA / mgPt, limiting current density ≥5.5 mA / cm 2 , half-wave potential ≥0.88V.
[0012] In a second aspect, the present application provides a method for preparing the ordered platinum alloy catalyst according to any one embodiment of the first aspect, the method comprising:
[0013] Mixing a salt solution containing platinum, a salt solution containing M, and a solution of a polymer additive to obtain a first mixed solution;
[0014] adding a salt solution containing M* to the first mixed solution to obtain a second mixed solution;
[0015] dispersing the carbon carrier in the second mixed liquid to obtain a third mixed liquid;
[0016] removing the solvent in the third mixed liquid to obtain a precursor;
[0017] The precursor is heat-treated in a reducing atmosphere to obtain a catalyst.
[0018] Optionally, the temperature of the heat treatment is 250°C to 450°C, and the insulation time of the heat treatment is 2h to 6h.
[0019] Optionally, the reducing atmosphere is a mixture of H2 and Ar, and the concentration of H2 is 2% to 10%.
[0020] Optionally, the polymer additive includes: one or more of lignin, methyl cellulose and dopamine.
[0021] In a third aspect, the present application provides a fuel cell, comprising the ordered platinum alloy catalyst described in any one embodiment of the first aspect.
[0022] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0023] The present application provides an ordered platinum alloy catalyst, comprising: a core, the core being a composite of a PtMM* alloy and C, wherein M is a non-precious metal and M* is a low-melting-point metal; and a shell, the shell being coated on at least part of the surface of the core, the shell being a carbon layer. First, by adding a low-melting-point metal element to the ordered platinum alloy catalyst, the bonding strength between platinum and the alloy component can be reduced, thereby reducing the formation energy Ea corresponding to the formation of the ordered alloy, reducing the ordered transition temperature, and finally achieving heat treatment at low temperature to obtain an ordered alloy, thereby avoiding the agglomeration and growth of alloy particles to the greatest extent. Secondly, by forming a carbon coating on the outer layer of the PtMM* alloy particles, the sintering and agglomeration growth of metal particles can be effectively avoided during the heat treatment process. Finally, a carbon-supported platinum alloy catalyst is prepared by coupling the two, and the agglomeration and growth of the Pt alloy can be avoided in the process of the Pt alloy catalyst forming an ordered structure, thereby ensuring a small and uniform particle size. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0026] Figure 1 A schematic flow chart of a method for preparing an ordered platinum alloy catalyst provided in an embodiment of the present application;
[0027] Figure 2 This is a comparison chart of the linear voltammetric scanning curves provided in Examples 1 and 2 of the present application and the comparative example. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0029] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0030] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "the following at least one item (items)" or similar expressions refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.
[0031] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0032] The creative ideas of this application are:
[0033] In order to improve the durability and stability of Pt alloy catalysts, it is necessary to construct an ordered structure of intermetallic compounds, which are characterized by low formation energy and high cohesive energy, and can be more suitable for fuel cell membrane electrode working conditions. However, in the process of forming an ordered structure, it is necessary to overcome extremely high diffusion energy barriers, so it must rely on high-temperature heat treatment to achieve it. High-temperature heat treatment can easily cause the agglomeration and growth of Pt alloys, thereby reducing the electrochemical active area and mass activity of the catalyst, and causing the batch consistency of the catalyst to decrease.
[0034] In order to solve the above technical problems, the present application creatively prepares platinum alloy catalysts by coupling polymer additives and low melting point metal elements. On the one hand, polymer additives can effectively improve the dispersibility of platinum alloy nanoparticles on the carrier. They form a protective layer by adsorbing on the surface of nanoparticles to prevent direct contact and agglomeration between particles. This dispersion effect helps to increase the active area of the catalyst and improve the catalytic efficiency. At the same time, polymer additives can also improve the stability of platinum alloy catalysts. During high temperature treatment, polymer additives can inhibit the migration and growth of nanoparticles and keep the microstructure of the catalyst stable. In addition, they can also enhance the interaction between nanoparticles and carriers to prevent the catalyst from falling off or deactivating during use. Therefore, polymer additives can achieve carbon coating of catalyst particles, thereby effectively avoiding sintering and agglomeration growth of metal particles during heat treatment. On the other hand. After low melting point metal elements (such as zinc, tin, etc.) form alloys with platinum, the electronic structure and surface properties of platinum can be changed, thereby improving the catalytic activity and selectivity of the catalyst. The alloying effect can also enhance the adsorption capacity of the catalyst to the reactants and promote the catalytic reaction. At the same time, low-melting-point metal elements are easily melted at high temperatures and diffuse between platinum nanoparticles to form a thin alloy layer. This alloy layer can effectively prevent the agglomeration and growth of platinum nanoparticles and maintain a uniform particle size distribution of the catalyst. In particular, the introduction of low-melting-point metals can reduce the bonding strength between platinum and alloy components, thereby reducing the formation energy Ea corresponding to the formation of ordered alloys, reducing the ordered transition temperature, and ultimately achieving the goal of obtaining ordered alloys by heat treatment at low temperatures, which avoids the agglomeration and growth of alloy particles to the greatest extent, and jointly ensures the stable preparation of ordered platinum alloy nanoparticles.
[0035] Therefore, by coupling polymer additives and low-melting-point metal elements to synergistically assist in the preparation of platinum alloy catalysts, the preparation of ordered alloys can be achieved through heat treatment at lower temperatures, thereby ensuring a smaller and uniform particle size, which can achieve higher performance and better durability in fuel cell applications and effectively reduce the consumption of precious metal platinum.
[0036] The present application provides an ordered platinum alloy catalyst, the catalyst comprising:
[0037] A core, wherein the core is a composite of a PtMM* alloy and C, wherein M is a non-precious metal and M* is a low melting point metal; and
[0038] The outer shell is coated on at least a portion of the surface of the inner core, and the outer shell is a carbon layer.
[0039] In some embodiments, the non-precious metal includes one or more of aluminum, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc and germanium.
[0040] In some embodiments, the low melting point metal includes one or more of gallium, indium, tin and bismuth.
[0041] In some embodiments, the molar ratio of Pt, M and M* is (3-13):(0.5-1.5):(0.5-1.5).
[0042] In the above-mentioned embodiment, the molar ratio of Pt, non-precious metal elements and low-melting-point metal elements is controlled to be Pt:M:M*=(3-13):(0.5-1.5):(0.5-1.5). On the one hand, Pt is the main active ingredient, and the addition of non-precious metal elements can reduce the cost of the catalyst, and at the same time, the stability and / or selectivity of the catalyst may be improved through the alloying effect. The addition of low-melting-point metal elements is mainly to utilize their fluidity at high temperatures to inhibit the agglomeration and growth of Pt nanoparticles. In addition, low-melting-point metal elements may also improve the performance of the catalyst through the alloying effect. Controlling the molar ratio of the three can ensure the catalytic performance of the catalyst while reducing the cost. On the other hand, non-precious metal elements and low-melting-point metal elements are easily dissolved and precipitated from the catalyst system, reducing its durability, so it is necessary to control the content of their elements to be lower than Pt, thereby ensuring the structural stability of the catalyst. Illustratively, the molar ratio of Pt, the non-precious metal element, and the low melting point metal element can be 3:1:1, 4:1:1, 5:1:1, 6:1:1, 7:1:1, 8:1:1, 9:1:1, 10:1:1, 11:1:1, 12:1:1, 13:1:1, and the like.
[0043] In some embodiments, the catalyst satisfies at least one of the following properties: particle size <5 nm, mass activity ≥400 mA / mgPt, limiting current density ≥5.5 mA / cm 2 , half-wave potential ≥0.88V.
[0044] The present application proposes a Pt alloy catalyst with a smaller and more uniform particle size that can be heat-treated at low temperature, and the method can be applied to a series of Pt alloy catalysts with different doping elements, with high universality. The prepared catalyst-carrying MEA has an output power density higher than Pt / C at the same Pt loading, and can be used as a fuel cell catalyst with lower cost and better performance.
[0045] Figure 1 A schematic flow chart of a method for preparing an ordered platinum alloy catalyst provided in an embodiment of the present application.
[0046] See also Figure 1 Based on a general inventive concept, the present application provides a method for preparing an ordered platinum alloy catalyst as described in any one of the above embodiments, the method comprising:
[0047] S1, mixing a salt solution containing platinum, a salt solution containing M, and a solution of a polymer additive to obtain a first mixed solution;
[0048] S2, adding a salt solution containing M* to the first mixed solution to obtain a second mixed solution;
[0049] S3, dispersing the carbon carrier in the second mixed solution to obtain a third mixed solution;
[0050] S4, removing the solvent in the third mixed liquid to obtain a precursor;
[0051] S5. In a reducing atmosphere, heat-treating the precursor to obtain a catalyst.
[0052] In some embodiments, the platinum-containing salt solution is an aqueous solution of chloroplatinic acid, the M-containing salt solution is an aqueous solution of a chloride salt or acetylacetonate salt (nitrates are used for copper and zinc) of aluminum, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, or germanium, the solution of the polymer additive is a water or acetone solution of the polymer additive, and the M*-containing salt solution is an aqueous solution of a chloride salt of gallium Ga, indium In, tin Sn, or bismuth Bi.
[0053] It should be noted that, according to the solution mixing order of the present application, the negatively charged groups in the polymer additive can first partially replace the chloride ions in chloroplatinic acid to coordinate with Pt, and the carboxyl groups and other groups in the polymer additive can coordinate with alloy components such as Co, etc., to form a bimetallic complex network. Further, a low melting point metal component and a carbon carrier are added to the system.
[0054] In some embodiments, the carbon support includes one or more of a mesoporous carbon support, a Ketjen black carbon support, and a solid carbon support.
[0055] In some embodiments, the mass ratio of carbon support to Pt is 5:(1-3). (The Pt loading is controlled to be 20%-60%).
[0056] In some embodiments, the mass ratio of the polymer additive to the Pt atom is 1:(1-5).
[0057] In some embodiments, the temperature of the heat treatment is 250° C. to 450° C., and the holding time of the heat treatment is 2 h to 6 h.
[0058] In the above embodiment, during the heat treatment process, chloroplatinic acid, salts of non-precious metals and low-melting-point metals are reduced to metal atoms by hydrogen, and lignin, methyl cellulose, and dopamine are converted into carbon layers and wrap PtMM* / C. At the same time, the platinum alloy catalyst is prepared by the synergistic assistance of polymer additives and low-melting-point metal elements, so that the catalyst can achieve the preparation of ordered alloys through heat treatment at a lower temperature, thereby avoiding the agglomeration and growth of Pt alloys. Exemplarily, the heat treatment temperature is 250°C, 270°C, 290°C, 300°C, 320°C, 350°C, 380°C, 400°C, 450°C, etc., and the heat treatment holding time can be 2.0h, 2.5°C, 3.0°C, 3.5°C, 4.0°C, 4.5°C, 5.0°C, 6.0h, etc.
[0059] In some embodiments, the reducing atmosphere is a mixture of H2 and Ar, and the concentration of H2 is 2% to 10%.
[0060] In the above embodiment, during the heat treatment, chloroplatinic acid, salts of non-precious metals and low-melting-point metals are reduced to metal atoms by hydrogen, and lignin, methylcellulose, and dopamine are converted into carbon layers and wrap PtMM* / C. Exemplarily, the concentration of H2 can be 2%, 3%, 5%, 7%, 9%, 10%, etc.
[0061] In some embodiments, the polymer additive includes: one or more of lignin, methyl cellulose and dopamine.
[0062] In some embodiments, vacuum filtration or rotary evaporation is used to remove the solvent in the reaction system.
[0063] The product prepared by the preparation method of the ordered platinum alloy catalyst is the above-mentioned ordered platinum alloy catalyst. The chemical composition and microstructure of the ordered platinum alloy catalyst prepared by the preparation method of the ordered platinum alloy catalyst can refer to the above-mentioned embodiment. Since the preparation method of the ordered platinum alloy catalyst adopts part or all of the technical solutions of the ordered platinum alloy catalyst embodiment, it has at least all the beneficial effects brought by the technical solutions of the ordered platinum alloy catalyst embodiment, which will not be repeated here one by one.
[0064] Based on a general inventive concept, the present application provides a fuel cell, which includes the ordered platinum alloy catalyst described in any one of the above embodiments.
[0065] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0066] Example 1
[0067] This embodiment provides a method for preparing an ordered platinum alloy catalyst, comprising the following steps:
[0068] 1) 32.4 mL of chloroplatinic acid aqueous solution (containing 3210 mg of chloroplatinic acid) and 10 mL of cobalt chloride aqueous solution (containing 622.4 mg of cobalt chloride hexahydrate) were added successively to 20 mL of aqueous solution containing 900 mg of methyl cellulose to obtain a first mixed solution.
[0069] 2) Add 10 mL of an aqueous solution containing 495 mg of stannous chloride to the first mixed solution (wherein the amounts of chloroplatinic acid and the other two salts added are controlled so that the molar ratio of platinum atoms to cobalt atoms to tin atoms is 3:1:1) to obtain a second mixed solution.
[0070] 3) 1 g of the mesoporous carbon carrier (BMC-8) was added to the second solution, and stirring was continued at room temperature for 12 h to obtain a third mixed solution.
[0071] 4) The solvent in the reaction system of the third mixed liquid is removed by rotary evaporation to obtain a metal-loaded precursor.
[0072] 5) The precursor was heat treated in a H2 / Ar mixed gas (H2 concentration was 5%) at 400°C for 4 h, and finally an ordered PtCoSn alloy catalyst was prepared at low temperature.
[0073] Example 2
[0074] This embodiment provides a method for preparing an ordered platinum alloy catalyst, comprising the following steps:
[0075] 1) 32.4 mL of chloroplatinic acid aqueous solution (containing 3210 mg of chloroplatinic acid) and 10 mL of nickel acetylacetonate aqueous solution (containing 670 mg of nickel acetylacetonate) were successively added to 20 mL of aqueous solution containing 800 mg of lignin to obtain a first mixed solution.
[0076] 2) Add 10 mL of an aqueous solution containing 495 mg of stannous chloride to the first mixed solution (wherein the amounts of chloroplatinic acid and the other two salts added are controlled so that the molar ratio of platinum atoms to nickel atoms to tin atoms is 3:1:1) to obtain a second mixed solution.
[0077] 2) 1 g of high specific surface area carbon support (ECP-600JD) was added to the second mixed solution, and stirring was continued at room temperature for 12 h to obtain a third mixed solution.
[0078] 3) The solvent in the reaction system of the third mixed liquid is removed by rotary evaporation to obtain a metal-loaded precursor.
[0079] 4) The precursor was heat treated in a H2 / Ar mixed gas (H2 concentration was 5%) at 350°C for 4 h, and finally an ordered PtNiSn alloy catalyst was prepared at low temperature.
[0080] Comparative Example 1
[0081] The commercial Pt / C was purchased from Tanaka Precious Metals of Japan, model E50E.
[0082] Comparative Example 2
[0083] This comparative example provides a method for preparing an ordered platinum alloy catalyst, comprising the following steps:
[0084] 1) 32.4 mL of chloroplatinic acid aqueous solution (containing 3210 mg of chloroplatinic acid) and 10 mL of cobalt chloride aqueous solution (containing 622.4 mg of cobalt chloride hexahydrate) were added successively to 20 mL of aqueous solution containing 900 mg of methyl cellulose to obtain a first mixed solution.
[0085] 3) 1 g of mesoporous carbon support (BMC-8) was added to the first solution, and stirring was continued at room temperature for 12 h to obtain a second mixed solution.
[0086] 4) The solvent in the reaction system of the second mixed liquid is removed by rotary evaporation to obtain a metal-loaded precursor.
[0087] 5) The precursor was heat treated in a H2 / Ar mixed gas (H2 concentration was 5%) at 900°C for 2 h to obtain an ordered PtCo alloy catalyst.
[0088] Comparative Example 3
[0089] This comparative example provides a method for preparing an ordered platinum alloy catalyst, comprising the following steps:
[0090] 1) 32.4 mL of chloroplatinic acid aqueous solution (containing 3210 mg of chloroplatinic acid) and 10 mL of cobalt chloride aqueous solution (containing 622.4 mg of cobalt chloride hexahydrate) were mixed to obtain a first mixed solution.
[0091] 2) Add 10 mL of an aqueous solution containing 495 mg of stannous chloride to the first mixed solution (wherein the amounts of chloroplatinic acid and the other two salts added are controlled so that the molar ratio of platinum atoms to cobalt atoms to tin atoms is 3:1:1) to obtain a second mixed solution.
[0092] 3) 1 g of the mesoporous carbon carrier (BMC-8) was added to the second solution, and stirring was continued at room temperature for 12 h to obtain a third mixed solution.
[0093] 4) The solvent in the reaction system of the third mixed liquid is removed by rotary evaporation to obtain a metal-loaded precursor.
[0094] 5) The precursor was heat treated in a H2 / Ar mixed gas (H2 concentration was 5%) at 400°C for 4 h to obtain an ordered PtCoSn alloy catalyst.
[0095] The alloy catalysts obtained in Examples 1 to 2 and Comparative Examples 1 to 3 were tested for performance, and the results are shown in Table 1.
[0096] Table 1 Performance test results of alloy catalysts obtained in Examples 1 to 2 and Comparative Examples 1 to 3
[0097]
[0098]
[0099] Figure 2 The linear voltammetric scanning curve comparison diagram provided by Examples 1 and 2 of the present application and the comparative example. Figure 2 It can be seen that the PtCoSn alloy catalyst and the PtNiSn alloy catalyst in the embodiment have higher mass activity, greater limiting current density, and higher half-wave potential than those in the comparative example.
[0100] In addition, one or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0101] In the embodiments of the present invention, a Pt alloy catalyst having a smaller and more uniform particle size is proposed which can be heat treated at low temperature, and the method can be applied to a series of Pt alloy catalysts with different doping elements, and has a high degree of universality. The prepared catalyst-carrying MEA has an output power density higher than that of Pt / C at the same Pt loading, and can be used as a fuel cell catalyst with lower cost and better performance.
[0102] In the embodiment of the present invention, the particle size of the ordered alloy catalyst provided is less than 5nm, the mass activity is ≥400mA / mgPt, and the limiting current density is ≥5.5mA / cm 2 , half-wave potential ≥0.88V.
[0103] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. An ordered platinum alloy catalyst, characterized in that: The catalyst comprises: A core, wherein the core is a composite of a PtMM* alloy and C, wherein M is a non-precious metal and M* is a low melting point metal; and The outer shell is coated on at least a portion of the surface of the inner core, and the outer shell is a carbon layer.
2. The catalyst according to claim 1, characterized in that The non-precious metals include: one or more of aluminum, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc and germanium.
3. The catalyst according to claim 1, characterized in that The low melting point metal includes one or more of gallium, indium, tin and bismuth.
4. The catalyst according to claim 1, characterized in that The molar ratio of Pt, M and M* is (3-13):(0.5-1.5):(0.5-1.5).
5. The catalyst according to claim 1, characterized in that The catalyst meets at least one of the following properties: particle size <5nm, mass activity ≥400mA / mg Pt , limiting current density ≥5.5mA / cm 2 , half-wave potential ≥0.88V.
6. A method for preparing the ordered platinum alloy catalyst according to any one of claims 1 to 5, characterized in that: The method comprises: Mixing a salt solution containing platinum, a salt solution containing M, and a solution of a polymer additive to obtain a first mixed solution; adding a salt solution containing M* to the first mixed solution to obtain a second mixed solution; dispersing the carbon carrier in the second mixed liquid to obtain a third mixed liquid; removing the solvent in the third mixed liquid to obtain a precursor; The precursor is heat-treated in a reducing atmosphere to obtain a catalyst.
7. The method according to claim 6, characterized in that The temperature of the heat treatment is 250° C. to 450° C., and the insulation time of the heat treatment is 2 h to 6 h.
8. The method according to claim 6, characterized in that The reducing atmosphere is a mixture of H2 and Ar, and the concentration of H2 is 2% to 10%.
9. The method according to claim 6, characterized in that The polymer additive includes: one or more of lignin, methyl cellulose and dopamine.
10. A fuel cell, characterized in that: The fuel cell comprises the ordered platinum alloy catalyst according to any one of claims 1 to 5.
Citation Information
Cited By
Platinum-germanium-based intermetallic ordered alloy catalyst as well as preparation method and application thereof
CN120715228A
Carbon-supported high-entropy alloy catalyst and preparation method thereof
CN121331849A
